Analisis Keterampilan Berbahasa pada Siswa Autisme Level 1 di SDN Perumnas 5 Kota Tangerang - Septy Nurfadhillah; Hartika Rhea Elita Immawan; Tasya Nurfadila Khoirunnisa (Lembaga Yasin AlSys, 2022)
Education can shape and develop the skills, attitudes, and intelligence of children to become intelligent, skilled and noble human beings. However, there are still many children who have not received proper education due to physical and mental limitations. One of them is autism, which is a serious developmental disorder that interferes with the ability to communicate and interact. The problem in this study focuses on the language skills of one of the Autism level 1 (mild) students at SDN Perumnas 5 Tangerang City. The purpose of this study was to describe Autism and learning in language skills from the learning strategies used by Special Guidance Teachers (GPK) at SDN Perumnas 5 Tangerang City. The research method uses a qualitative approach with a descriptive method. The research site is at SDN Perumnas 5 Tangerang City. Data collection techniques using observation, interviews and documentation. While the data analysis technique of this research uses the theory of Miles and Huberman, which includes data reduction, data presentation and conclusions/verification. To test the validity of the data by using triangulation. The results of research conducted by observing and interviewing Mrs. Yanti as a Special Advisor Teacher (GPK) at SDN Perumnas 5, researchers are interested in examining language skills and learning strategies in level 1 autism students.